2014
DOI: 10.1155/2014/874132
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Nanofluids in Differentially Heated Enclosure Undergoing Orthogonal Rotation

Abstract: Natural convection heat transfer in a rotating, differentially heated enclosure is studied numerically in this paper. The rotating enclosure is filled with water-Ag, water-Cu, water-Al 2 O 3 , or water-TiO 2 nanofluids. The governing equations are in velocity, pressure, and temperature formulation and solved using the staggered grid arrangement together with MAC method. The governing parameters considered are the solid volume fraction, 0.0 ≤ ≤ 0.05, and the rotational speeds, 3.5 ≤ Ω ≤ 17.5 rpm, and the centri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Comparison of computed isotherms between present work (left) with Tso et al[21] (middle) and Saleh et al[22] (right) results under (a) φ = 0, Ra = 3 × 10 5 , Ω = 17.5 rpm, (b) φ = 3π/2, Ra = 3 × 105 , Ω = 15.5 rpm, and (c) φ = π, Ra = 3 × 10 5 , Ω = 17.5 rpm.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Comparison of computed isotherms between present work (left) with Tso et al[21] (middle) and Saleh et al[22] (right) results under (a) φ = 0, Ra = 3 × 10 5 , Ω = 17.5 rpm, (b) φ = 3π/2, Ra = 3 × 105 , Ω = 15.5 rpm, and (c) φ = π, Ra = 3 × 10 5 , Ω = 17.5 rpm.…”
mentioning
confidence: 62%
“…In addition, a natural convection in a rotation system with respect to a horizontal axis, which was an ideal case for the rolling motion in this research, was employed to validate the flow and heat transfer. The numerical results were compared with those calculated by Tso et al [21] (middle) and the experimental data performed by Saleh et al [22] (right), as shown in Figure 7. It was found that the numerical results agree well with the results in the literature.…”
Section: Model Validationmentioning
confidence: 96%
“…Fundamental study on the natural convection in rotation systems mainly concerned the constant-velocity rotation system, which is a special case for the harmonic rotation in this research. In these researches, the cavities rotate about either a horizontal axis [9][10][11][12][13][14][15] (orthogonal to the gravity axis) or a vertical axis [16][17][18][19]. These vertical rotations are the special cases (constant angular velocity) of yawing motion, which will be investigated in this study.…”
Section: Fundamental Researchesmentioning
confidence: 99%